Pro-Inflammatory Cytokines IL-1β and TNF-α are not Associated with Plasma Homocysteine Concentration in Alzheimer's Disease - Veryard, Leon; Jones, Emma; Weaving, Gary; Smith, Edward; Cheek, Liz; Wickramasinghe, Anuprabha; Tabet, Naji (Current Alzheimer Research, 2013)
Increased concentrations of pro-inflammatory blood cytokines and plasma homocysteine (Hcy) are frequently reported in Alzheimer's disease (AD). Hcy appears to have immunomodulating and pro-inflammatory activities. Further, emerging evidence from animal and non-AD human studies implicates Hcy in potentiating the activities of proinflammatory cytokines; Hcy toxicity may also, in part, be mediated by these cytokines. As little is known about the potential relationship between these inflammatory markers specific to AD, the aim of this study was to assess potential impact of Hcy on the widely reported increases in cytokine concentrations in AD. Blood concentrations of two proinflammatory cytokines, IL-1β and TNF-α, along with Hcy were assessed in 40 AD patients and 30 cognitively intact controls. Mean blood concentrations of IL-1β and TNF-α differed significantly between the AD and control groups (p=0.001 and p<0.001 resp). This difference survived adjustment for age and gender on logistic regression. Hcy was significantly correlated with age only in the patient (rs=0.38, p=0.02) but not the control group. There was no significant correlation between IL-1β and Hcy, and between TNF-α, and Hcy in either the AD or the control group. Hence, our AD data did not replicate results obtained from animal and non-AD human studies which have linked pro-inflammatory cytokines concentrations to Hcy. A different inflammatory focus may exist in AD which may be influenced at least in a significant part by non-vascular pathogenesis. However, these results indirectly support the notion that the observed mild hyperhocysteinemia in AD may be due to non-inflammatory factors.
Keywords: IL-1beta